Investigation of Supplier Selection Criteria that Leads to Buyer-Supplier Long Term Relationship for Semiconductor Industry - Yogeswaran Vijayakumar; Suzari Abdul Rahim; Aidi Ahmi; Nor Aida Abdul Rahman (International Journal of Supply Chain Management, 2019)
Selecting the right supplier has been the greatest challenge in supply chain management (SCM) in many industries. Large spool of suppliers in industry and diversity of purchasing scope causes a wide variety of supplier selection criteria. The right strategy in fixing the criteria for supplier selection is crucial, to ensure smooth supply chain operation. It is believed that in SCM, a good relationship with suppliers will further benefit the operations of both buyers and suppliers. This research attempts to investigate the supplier selection criteria that leads to buyer-supplier long term relationship, especially for the semiconductor industry in Penang, Malaysia. In this study, the focus is to identify the critical supplier selection criteria such as supplier quality, performance delivery, supply service, cost and estimate their influence towards buyer’s satisfaction which later on, narrate a path for a buyer-supplier long term relationship. Two hundred eighty-eight respondents with a minimum one year of working experience in handling suppliers in the semiconductor industry in Penang, Malaysia, participated in this research. Smart PLS was used to conduct hypotheses testing while confirming the validity and reliability of the data collected from the survey. The finding of this research shows that supplier quality, performance delivery, and supply service criteria are significant for the buyer-supplier long term relationship. The outcome of this research will help semiconductor companies to have a set of best criteria for supplier selection. Later, it could help them establish long term relationship with the supplier to benefit their supply chain operations, and at the same time ensuring the growth, survival and sustainability of their supplier business.